Ombudsman's role in supervising maladministration: A study based on law No. 37 of 2008 and siyāsah dustūriyyah - Amalia Dwi Prihanti (Green Governance: Exploring Politics, Social Justice, and the Environment, 2025)
Background: The Ombudsman plays a critical role in overseeing public service delivery and government administration, particularly in addressing maladministration. In 2022, the Ombudsman investigated alleged maladministration in the appointment of acting regional heads, following reports from KontraS, ICW, and Perludem, which highlighted a lack of public participation, transparency, and procedural deviations. This study examines the Ombudsman's role and authority in addressing maladministration based on Law No. 37 of 2008, viewed through the lens of siyāsah dustūriyyah (Islamic constitutional politics). Methods: This research employs a normative juridical approach, utilizing library research to analyze legal regulations, books, and other relevant sources. The study adopts a statutory approach (statute approach) and a conceptual approach (conceptual approach) to explore the Ombudsman's role and authority. Findings: The Ombudsman's actions in addressing maladministration include conducting independent investigations, issuing recommendations, and publishing findings in the Final Examination Report/Laporan Akhir Hasil Pemeriksaan (LAHP). These actions align with its authority under Articles 7 and 8(1) of Law No. 37 of 2008. From the perspective of siyāsah dustūriyyah, the Ombudsman's role parallels that of ḥisbah, an Islamic supervisory institution tasked with upholding justice and preventing wrongdoing. Conclusion: The Ombudsman ensures transparency, accountability, and adherence to legal procedures in government administration. Its authority, as outlined in Law No. 37 of 2008, aligns with the principles of siyāsah dustūriyyah, emphasizing the importance of supervisory institutions in promoting good governance. Novelty/Originality of this article: This study uniquely integrates the legal framework of the Ombudsman with the principles of siyāsah dustūriyyah, offering a comprehensive analysis of the Ombudsman's role in addressing maladministration from both legal and Islamic governance perspectives.